2011
DOI: 10.1002/icd.701
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐cultural examination of Aboriginal and European Canadian mothers' beliefs regarding proactive and reactive aggression

Abstract: The purpose of the present study was to examine the maternal beliefs and practices regarding preschool children's proactive and reactive aggression, within a cross-cultural framework. Participants included 30 Aboriginal and 45 European Canadian mothers of preschoolers who provided their emotional reactions, causal attributions, socialization strategies, and parenting goals in response to children's aggressive behaviours. Results supported previous research that both groups of mothers generally responded negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 59 publications
4
18
0
Order By: Relevance
“…Partially supporting our expectations and previous research on preschoolers (Cheah & Sheperd, ), the frequency of mothers' socialization strategies varied between proactive and reactive aggression. Specifically, our findings suggested that mothers used more indirect strategies (e.g., asking the child, teacher, or other children to find out more about the aggressive episode) and endorsed other‐oriented strategies (e.g., ‘telling the other child to behave properly because her child is not the only one who behaved inappropriately’ or ‘making sure that the mother of the other child is informed’) to intervene with reactive aggression.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Partially supporting our expectations and previous research on preschoolers (Cheah & Sheperd, ), the frequency of mothers' socialization strategies varied between proactive and reactive aggression. Specifically, our findings suggested that mothers used more indirect strategies (e.g., asking the child, teacher, or other children to find out more about the aggressive episode) and endorsed other‐oriented strategies (e.g., ‘telling the other child to behave properly because her child is not the only one who behaved inappropriately’ or ‘making sure that the mother of the other child is informed’) to intervene with reactive aggression.…”
Section: Discussionsupporting
confidence: 89%
“…Together, these findings suggest that mothers become more emotionally reactive when the aggressive act includes physical harm and is initiated by their own child. In line with Cheah and Sheperd's () findings, in the current study, we argued that Turkish mothers would perceive reactive aggression as a defensive reaction. Therefore, we expected that they would report feeling more negatively towards children's engagement in proactive aggression than reactive aggression.…”
Section: Parenting Beliefs and Behaviours In The Turkish Cultural Consupporting
confidence: 90%
See 3 more Smart Citations